Fundamentals of nursing : clinical companion - Potter, Patricia Ann; Perry, Anne Griffin; Stockert, Patricia A.; Hall, Amy (Amy M.) (St. Louis, Missouri : Elsevier, 2023)
Learn the concepts and skills and develop the clinical judgment you need to provide excellent nursing care! Fundamentals of Nursing, 11th Edition prepares you to succeed as a nurse by providing a solid foundation in critical thinking, clinical judgment, nursing theory, evidence-based practice, and patient-centered care in all settings. With illustrated, step-by-step guidelines, this book makes it easy to learn important skills and procedures. Care plans are presented within a nursing process framework that is coordinated with clinical judgement, and case studies show how to apply concepts to nursing practice. From an expert author team led by Patricia Potter and Anne Perry, this bestselling nursing textbook helps you develop the understanding and clinical judgment you need to succeed in the classroom and in your career.
Includes bibliographical references and index.
Keywords: Nursing -- Textbooks; Nursing -- Practice -- Textbooks; Nurse and patient; Nursing; Nurse-Patient Relations; Relations infirmière-patient.; Nurse and patient; Nursing; Nursing -- Practice; Textbooks; Textbooks